Mitochondrial ribosomal protein S9M is involved in male gametogenesis and seed development in Arabidopsis. (10th April 2020) - Lu, C.; Xie, Z.; Yu, F.; Tian, L.; Hao, X.; Wang, X.; Chen, L.; Li, D.
Abstract: Mitochondrial function is critical for cell vitality in all eukaryotes including plants. Although plant mitochondria contain many proteins, few have been studied in the context of plant development and physiology. We used knock‐down mutant RPS9M to study its important role in male gametogenesis and seed development in Arabidopsis thaliana . Knock‐down of RPS9M in the rps9m‐3 mutant led to abnormal pollen development and impaired pollen tube growth. In addition, both embryo and endosperm development were affected. Phenotype analysis revealed that the rps9m‐3 mutant contained a lower amount of endosperm and nuclear proteins, and both embryo cell division and embryo pattern were affected, resulting in an abnormal and defective embryo. Lowering the level of RPS9M in rps9m‐3 affects mitochondrial ribosome biogenesis, energy metabolism and production of ROS. Our data revealed that RPS9M plays important roles in normal gametophyte development and seed formation, possibly by sustaining mitochondrial function. Abstract : RPS9M is involved in gametophyte development and seed formation by sustaining normal mitochondria function.